BONE MINERAL DENSITY DISORDER IN PATIENTS WITH DIGESTIVE DISEASES - Khusainova Munira Alisherovna; Ergashova Madina Muxtorovna; Toshtemirova Madina Oybekovna (Journals Park Publishing, 2024)
The article is devoted to the study of the clinical features of the course of diseases of the gastrointestinal tract and liver in the formation of osteopenia and osteoporosis. The data on the frequency of occurrence of bone mineral density disorders in patients with chronic pancreatitis, cirrhosis of the liver, cholelithiasis, inflammatory bowel diseases, as well as diseases accompanied by malabsorption syndrome (gluten enteropathy, short small intestine syndrome) are presented. The population (age, gender) has been established, decrease in body mass index, menopause), clinical and laboratory factors indicating a high risk of a decrease in bone mineral density in this category of patients.
Keywords: violation of bone mineral density; densitometry; biliary insufficiency; gallstone disease; chronic pancreatitis; malabsorption syndrome; cirrhosis of the liver.